A comparative analysis of the effectiveness of active versus passive atrial lead fixation in Chinese patients with cardiac implantable electrical devices: a long term, retrospective, observational, single-center study. (4th March 2017) - Hao, Yinglu; Li, Yanping; Liao, Derong; Yang, Ling; Liu, Fangyan
Abstract: Background: Data comparing active atrial lead fixation with passive atrial lead fixation in Chinese patients with cardiovascular implantable electronic devices (CIEDs) for atrial pacing is limited. Our study evaluated the effectiveness of active fixation versus passive fixation of atrial leads by observing the lead performance parameters. Methods: This retrospective, long-term, single-center study included a cohort of Chinese patients who underwent CIED implantation at the Department of Cardiology of People's Hospital of Yuxi City, China, from 1 March 2010 to 1 March 2015. Efficacy was determined by comparing implantation time, threshold values, incidence of lead dislocation/failure, and lead-related complications between the two groups. Results: Of the 1217 patients, active and passive atrial lead fixation were performed in 530 (mean age, 69.37 ± 11.44 years) and 497 (mean age, 68.33 ± 10.96 years). The active fixation group reported significantly lower mean atrial implantation times ( P  = .0001) and threshold values ( P  = .044) compared with the passive atrial lead fixation group. In addition, threshold values in the active atrial lead fixation group were stable throughout the observation period. No instances of myocardial perforation, cardiac tamponade, implantation failure, or electrode dislocation/re-fixation were reported in the active atrial lead fixation group. A favorable decrease in patient comfort parameters such as bed rest time ( P  = .027) and duration of hospital stay ( P  = .038) were also observed in the active lead fixation group. Conclusion: Active atrial lead fixation demonstrated greater stability, steady long-term thresholds and minimal lead-related complications compared to passive lead fixation in Chinese patients with CIEDs.